(untitled) (Mustansiria Dental Journal, 2018)
The purposes of this in vitro study were to compare the marginal adaptation, internal fitness and the microleakage of three CAD-CAM all ceramic crowns materials: Zolid, Zircon, and Empress 2. This study also evaluated the correlation of microleakage of these ceramic crowns materials to the marginal fitness. Forty-five maxillary first premolar teeth were prepared with 2-mm occlusal reduction and 1-mm all around shoulder finish line, teeth were randomly divided into three main groups according to the type of ceramic material that was used (n=15). Group 1: received a CAD-CAM Ceramill Zolid® unilayered transparent zircon Group 2: received a CAD-CAM Ceramill ZI units (Zirconium oxide) Group 3: received a CAD-CAM Ceramill wax units that would subsequently invested and heat pressed to fabricate a hot-press ceramic crowns. The results showed statistical significant difference in marginal fitness, internal fitness and microleakage between Zolid group and other groups (P>0.0001). There was highly significant correlation of the marginal and internal fitness, whilst there was no significant correlation marginal fitness and microleakage. ,